Nonpolynomial Spline Method for Solving Linear Fractional Differential Equations - Hasan , Nabaa N. (International Journal of Psychosocial Rehabilitation, 2020)
The main objective of this paper define linear differential operator L of order n with its adjoint operator L* to solve L* L. = 0 to get non polynomial spline (generalized spline) basis. Different operators of order n, is used to get different basis of the method. "The efficiency of the method will be illustrated by solving test examples of linear fractional differential equations(LFDE) of order α", where 0